EPIDEMIOLOGICAL CHARACTERIZATION OF THE ASSOCIATION BETWEEN ARTERIAL HYPOTENSION AND OBESITY IN A FARMING POPULATION (Conferencea, 2023)
Obesity is considered one of the most important modifiable risk factors for arterial hypertension. However, there are almost no epidemiological studies specifically investigating the association between arterial hypotension (ArGt) and obesity. Since we set the goal of studying this issue in our dissertation work, we performed this research to get an idea about the features of identifying this leading risk factor of cardiovascular disease (CVD) in the modern rural population.